Metal Additive Manufacturing - State of the Art 2020 - Asnafi, Nader (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Additive Manufacturing (AM), more popularly known as 3D printing, is transforming the industry. AM of metal components with virtually no geometric limitations has enabled new product design options and opportunities, increased product performance, shorter cycle time in part production, total cost reduction, shortened lead time, improved material efficiency, more sustainable products and processes, full circularity in the economy, and new revenue streams. This Special Issue of Metals gives an up-to-date account of the state of the art in AM.